Penentuan Prioritas Kriteria Pada Proses Rekrutmen dan Seleksi Karyawan Menggunakan Metode Analytic Hierarchy Process di PT Citatah Tbk - Ikah Ikah; Risma Fitriani (Jurnal Serambi Engineering, 2022)
Abstract As the initial phase in the recruiting process, recruitment and selection must be done properly, efficiently, effectively, and objectively so that the hired personnel are qualified, have high credentials, and can perform their responsibilities according to their positions. Using the Analytic Hierarchy Process (AHP) technique, this study attempts to find the most important factors for employee acceptability at PT Citatah Tbk. Experience, education, age, psychological tests, skills, interviews, height, and location of recruiting jobs are some of the recruitment criteria employed by PT Citatah Tbk HR GA Department. Analytic Hierarchy Process (AHP) is a method for solving Multicriteria Decision Making (MCDM) problems using a decision support system. The results show that age is the first criterion in the employee recruitment process, with a weight of 0.2664, education is the second criterion with a weight of 0.2047, experience is the third criterion with a weight of 0.1495, skill is the fourth criterion with a weight of 0.1209, a psychological test is the fifth criterion with a weight of 0.0918, an interview is the sixth weight with a weight of 0.0728, the seventh weight, with a weight of 0.530, is length, and the eighth weight, with a weight of 0.0409, is the location of the recruiting position.Keywords: Recruitment, criteria, employee, analytic hierarchy process, selection. AbstrakRekrutmen dan seleksi sebagai langkah awal dalam proses penerimaan karyawan harus dilakukan secara akurat, efisien, efektif dan obyektif agar pegawai yang direkrut berkualitas, memiliki kualifikasi tinggi, dan mampu menjalankan tugas sesuai jabatannya. Tujuan dari penelitian ini adalah untuk menentukan kriteria prioritas perekrutan karyawan di PT Citatah Tbk dengan menggunakan salah satu metode Multi Criteria Decision Making (MCDM), yaitu Analytic Hierarchy Process (AHP). Penerapan metode MCDM tepat digunakan untuk menyelesaikan masalah multi kriteria seperti pada penelitian ini. Beberapa kriteria pada penerimaan karyawan yang digunakan oleh Departemen HR GA PT Citatah Tbk adalah pengalaman, pendidikan, usia, psikotes, keterampilan, wawancara, tinggi badan dan lokasi posisi rekrutmen. Hasil penelitian menunjukkan bahwa kriteria pertama saat merekrut karyawan adalah usia dengan bobot 0,2664, kedua pendidikan dengan bobot 0,2047, ketiga pengalaman dengan bobot 0,1495, keempat skill dengan bobot 0,1209, kelima adalah psikotes dengan bobot 0,0918, keenam interview dengan bobot 0,0728, ketujuh tinggi badan dengan bobot 0,530, dan kedelapan penempatan lokasi rekrutmen dengan bobot 0,0409.Kata Kunci: Rekrutmen, kriteria, karyawan, analytic hierarchy process, seleksi.